THE INFLUENCE OF ORGANIZATIONAL CULTURE, JOB SATISFACTION, AND PROFESSIONAL COMMITMENT ON INNOVATIVE BEHAVIOR OF FLIGHT INSTRUCTORS AT THE CIVIL FLIGHT SCHOOL IN INDONESIA - Afen Sena (Research and Development Agency of The Ministry of Transportation, 2020)
Abstract—In a dynamic and rapidly changing environment, innovation is the crucial factor for organizational success. Innovations that are needed primarily are innovations at the individual level or innovative behavior, which is a source of innovation at the organization level. This study aims to investigate the factors that influence the flight instructor's innovative behavior at flight schools in Indonesia, mainly based on organizational culture, job satisfaction, and professional commitment. The study used a quantitative approach with a survey method with a sample of 98 flight instructors taken through simple random sampling. Data collection is using a questionnaire with a five-point Likert scale and data analysis using path analysis. The findings in the study indicate that organizational culture, job satisfaction, and professional commitment have a positive direct effect on innovative behavior. Organizational culture is also indicating to have a positive direct effect on job satisfaction and professional commitment. Other findings show that job satisfaction does not directly effect on professional commitment. Based on the results of this study, the factors of organizational culture, job satisfaction, and professional commitment must be positioned as a strategic factor in the process of organizational management at flight schools in order to obtain sufficient attention. These three factors must also be continuously improved to strengthen innovative behavior among flight instructors.